2014
DOI: 10.1080/13557858.2014.890599
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differentials in under-five mortality in Nigeria

Abstract: Objective. There are huge regional disparities in under-five mortality in Nigeria. While a region within the country has as high as 222 under-five deaths per 1000 live births, the rate is as low as 89 per 1000 live births in another region. Nigeria is culturally diverse as there are more than 250 identifiable ethnic groups in the country; and various ethnic groups have different sociocultural values and practices which could influence child health outcome. Thus, the main objective of this study was to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 30 publications
1
49
1
1
Order By: Relevance
“…Contraceptive use was categorised as 1) currently using modern method or 2) not currently using modern method. These variables have been reported as important factors influencing child survival ( 22 , 23 ).…”
Section: Methods and Datamentioning
confidence: 99%
“…Contraceptive use was categorised as 1) currently using modern method or 2) not currently using modern method. These variables have been reported as important factors influencing child survival ( 22 , 23 ).…”
Section: Methods and Datamentioning
confidence: 99%
“…Previous studies have identified individual-, household-and community-level determinants of childhood mortality (Adedini, Odimegwu, Imasiku, & Ononokpono, 2014a;Akinyemi et al, 2015;Antai & Moradi, 2010), but death clustering has not been previously explored. Reports from an operational research study conducted in three Northern states of Nigeria (Jigawa, Yobe and Zamfara) revealed that more than 80% of child deaths were reported by only 20% of the women studied (Klouda & Adamu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, research shows that in the US, black women are three to four times more likely to die from pregnancy related causes than white women 7. In Nigeria, inequities are seen across ethnic and tribal differentials—for example, through significant disparities in mortality in children under 5 years 8…”
Section: Strengthen Rights Based Accountabilitymentioning
confidence: 99%